An overview of the numerical modeling, simulation, and optimization methods: toward the design of highly efficient planer perovskite solar cells - Mehdi Aliaghayee (Discover Electronics)
Abstract Perovskite solar cells (PSCs) have recently become one of the most encouraging thin-film photovoltaic (PV) technologies due to their superb characteristics, such as low-cost and high power conversion efficiency (PCE) and low photon energy lost during the light conversion to electricity. In particular, the planer PSCs have attracted increasing research attention thanks to their advantages, like hysteresis elimination, large-scale production processability, and having a certified PCE of over 26%. However, there are still some challenges to the development of these cells. To optimize and improve the performance of PSCs, the simulation analysis is as essential as the experimental study. This review intensively describes and discusses the numerical modeling, simulation, and optimization methods of direct n–i–p planer PSCs. This paper classifies the reviewed works based on which PSC’s layers are engineered and provides specific comments for each study. In addition, this study reviews other types of planer PSCs, including inverted p–i–n structures and charge transport layer-free configurations. Finally, with a critical outlook on the currently existing challenges and possible development opportunities, helpful research guidelines are proposed for further improvements.